SURVEI KETEPATAN PUKULAN DRIVE TOPSPIN DALAM PERMAINAN TENIS MEJA TINGKAT PEMULA PADA ATLET PUTRA PTM KEBUN NOPI KECAMATAN KUANTAN MUDIK - Gusdernawati, Aulia; Slamet, Slamet; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The ability to ride topspin is an attack on table tennis. the problem in this study is how the level of accuracy of the drive topspin punch in the beginner level of table tennis in male athletes PTM Kebun Nopi District Kuantan Mudik. This study aims to determine the level of accuracy of top spin thresholds in male athletes at PTM Kebun Nopi, Kuantan Mudik Subdistrict. This research is a quantitative descriptive research. The method used is a survey method. The population in this study was the male athletes of PTM Kebun Nopi, Kuantan Mudik Subdistrict, which consisted of 8 male athletes. The instrument used to measure the accuracy of Tomoliyus' top spin drive punch (2012: 11). Data analysis techniques show that: (1) The accuracy of the top spin of the forehand drive for male athletes at PTM Kebun Nopi, Kuantan Mudik Subdistrict was in the